A COMPREHENSIVE EVALUATION OF 'ACTIVE SMART POLYMERS “A SYSTEMATIC REVIEW AND FUTURE PERSPECTIVE” - Naser Hassan Rather; Faisal Abass Padder (RADJA PUBLIKA, 2023)
ABSTRACT Smart polymeric materials exhibit significant changes in their properties when subjected to minor changes in their surroundings. These environmental factors can include temperature, pH levels, chemicals, and light. These materials, which are sensitive to stimuli, can be either artificially created or naturally occurring. Over the past decade, the utilization of smart materials in various biological applications has gained significant importance. These applications encompass solving biological problems such as bio separation, drug delivery, biosensor design, tissue engineering, protein folding, and microfluidics. The objective of these endeavors is to imitate the intelligent behavior observed in biological systems and ultimately regulate complex systems like immune responses at desired levels. The remarkable versatility and untapped potential of smart polymeric materials position them as an exciting intersection between the fields of chemistry and biology.